IoT-Based Smart Farming System Design for Greenhouse Monitoring in Urban Areas - Marti Widya Sari; Erika Amalia; Prahenusa Wahyu Ciptadi; R. Hafid Hardyanto; Banu Santoso (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2026)
The rapid development of urban areas has led to a significant reduction in agricultural land, creating the need for innovative solutions to meet food demands, especially for fresh vegetables. One promising alternative is urban farming supported by the Internet of Things (IoT). This research aims to design and develop an IoT-based smart farming system for monitoring vegetable crops in urban areas with limited land availability. The system uses a NodeMCU ESP32 as the main controller, an SHT20 sensor to measure temperature and humidity, and a pH sensor to monitor the acidity of the nutrient solution. Sensor data are displayed in real time through an LCD and an Android-based application, and are also used to control an automatic fan to maintain optimal environmental conditions. The research method applied is an experimental approach comprising a literature review, system design, hardware and software implementation, and system testing. Based on the research results, the IoT-based smart farming system was successfully developed and can monitor plant environmental conditions and nutrient solutions in real time via an Android application, with data stored in a database and displayed appropriately. The test results indicate that the system helps users manage vegetable cultivation more efficiently. This system is expected to provide an effective, efficient, and sustainable smart farming solution for urban areas with limited land availability.